Motivasi Petani dalam Menerapkan Sistem Tanam Padi Jajar Legowo di Subak Taro Kaja, Desa Taro, Kecamatan Tegallalang - DEWI, SANG AYU MADE SRI UTAMI; ASTITI, NI WAYAN SRI; ANGGRENI, I GUSTI AYU AGUNG LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.1, Juli 2021, 2021)
Motivation of Farmers in Implementing Jajar Legowo Rice Planting System in Subak Taro Kaja, Taro Village, Tegallalang District Jajar Legowo 2: 1 planting system is an innovation that requires both intrinsic and extrinsic motivation of farmers in adopting, taking action, and implementing the rice planting system. This study aims to determine intrinsic motivation, extrinsic motivation and more dominant motivation to encourage farmers to implement the Jajar Legowo rice planting system in Subak Taro Kaja, Taro Village, Tegallalang District. The analytical method used in this study is descriptive qualitative and quantitative. The results show that the level of motivation of farmers in implementing the Jajar Legowo rice planting system is at high category with a score of 3,46 that is obtained from the intrinsic motivation score of 3,51 and extrinsic motivation score of 3,41. The more dominant motivation is intrinsic motivation, although both motivations are in the same category, namely high. It is recommended that Subak Taro Kaja coordinates with the Field Agricultural Extension Workers (PPL) in developing pest and disease prevention techniques. PPL should better understand the characteristics of farmers, gets more active in communicating and advising farmers. This study does not particularly look at the economic aspects of the matter and it is recommended future studies to pay attention to the variables and indicators of research.